Critical Role of Suspension Media in Electrophoretic Deposition: The Example of Low Loss Dielectric BaNd2Ti5O14 Thick Films - Vilarinho, Paula M.
The importance of electrophoretic deposition (EPD) is well recognized for thick film technology, but unfortunately there is no universal suspension medium for the EPD of oxides. Thus, the selection of the medium, the stability of the suspensions, and the control of the particle potentials, critical for a good deposition, need to be established for each new material being processed by EPD. In this article, we investigate the key parameters, studying the electrochemistry of BaNd2Ti5O14 (BNT) suspensions, and establish relationships between suspension media, EPD process conditions, microstructure of the deposits, and resulting electrical properties of the BNT films. Suspension stability of water, ethanol, acetic acid, and acetone-based media was analyzed in terms of zeta potential, particle size distribution, UV transmittance, and inductively coupled plasma spectrometry. The highest absolute zeta potential values determined for acetone with I-2 and acetic acid media are in good agreement with the high stability, small and narrow particle size distribution, and low UV light transmittance measured for these suspensions. Very high quality thick deposits were consequently achieved. However, it was demonstrated that aging of the acetic acid-based suspension have serious negative effects on the EPD process for BNT materials, including leaching of the metallic elements with a consequent modification of the material stoichiometry, change of the conductivity of the suspension, and degradation of the films microstructure. These facts severely restrict the use of acetic acid. Our results clearly indicate that, besides the stability of the suspension, the electrochemistry and aging behavior are key aspects for the EPD of functional oxides. Our systematic approach could be viewed as providing a set of guidelines for the development of EPD of other oxides.